পিরোজপুর জেলার মুক্তিযুদ্ধের ইতিহাস - ফিরোজ, কায়সার ১৯৪৪- (ঢাকা : গতিধারা, 2014)
Articles on the role and participation of Pirojpur District in the 1971 liberation movement of Bangladesh.
AAL
Development Book Agency
In Bengali.
Keywords: Nationalism -- Bangladesh -- Pirojpur District -- History; Pirojpur District (Bangladesh) -- Politics and government; Bangladesh -- History -- Revolution, 1971